2020
DOI: 10.4314/ovj.v10i1.5
|View full text |Cite
|
Sign up to set email alerts
|

The ophthalmic health and refractive state of working dogs in South Brazil

Abstract: Background: Working dogs, such as police dogs and guide dogs, have important roles in the contemporary society by performing specific and demanding jobs. Ocular health and the maintenance of good visual acuity are imperative to strong work performance and thus human safety. Aim: The aim of this study was to assess ophthalmic abnormalities and refractive errors in police and guide dogs in Brazil. Methods: A total of 71 dogs (141 eyes) were evaluated. Ten were guide dogs and 61 were police dogs. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The refractive state of eyes of various breed dogs was described in number of publications determining specific tendencies (Murphy et al 1992;Kubai et al 2008;Williams et al 2011;Groth et al 2013;Hernandez et al 2016;Balicka et al 2018;de Oliveira et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The refractive state of eyes of various breed dogs was described in number of publications determining specific tendencies (Murphy et al 1992;Kubai et al 2008;Williams et al 2011;Groth et al 2013;Hernandez et al 2016;Balicka et al 2018;de Oliveira et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ophthalmic diseases in police and military dogs were the cause of 1.4% of medical emergencies (Parr et al, 2013), 2.4% of discharges from service (Evans et al, 2007) and 11% of deaths and euthanasia . In a study of 71 service dogs (61 police, 10 handlers), eye abnormalities were found in 38 (54%) animals, the most common of which was primary cataract (Oliveira et al, 2020).…”
Section: Figure 5 Diseases Of the Visual And Hearing Organs In Servic...mentioning
confidence: 99%
“…Thus, ophthalmic diseases in police and military dogs were the cause of 1.4% of medical emergencies (Parr et al, 2013), 2.4% of discharges from service (Evans et al, 2007) and 11% of deaths and euthanasia . In a study of 71 service dogs (61 police, 10 handlers), eye abnormalities were found in 38 (54%) animals, the most common of which was primary cataract (Oliveira et al, 2020).…”
Section: Figure 5 Diseases Of the Visual And Hearing Organs In Servic...mentioning
confidence: 99%